2008
DOI: 10.1093/treephys/28.2.277
|View full text |Cite
|
Sign up to set email alerts
|

Annual and seasonal variations in photosynthetic capacity of Fagus crenata along an elevation gradient in the Naeba Mountains, Japan

Abstract: Canopy photosynthetic capacity, measured as leaf maximum carboxylation rate (V (cmax)), is a key factor in ecosystem gas exchange models applied at different scales. We report seasonal and interannual variations in V(cmax) of natural beech stands (Fagus crenata Blume) along an altitudinal gradient in the temperate climate zone of Japan. Estimates are based on 6 years of gas exchange measurements. Pronounced seasonal and interannual variations in V(cmax) normalized to 25 degrees C (V(c,25)) were found for sun l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 34 publications
5
41
1
Order By: Relevance
“…All these parameters were similar for healthy and declining trees. Similarly, the observed phenological variations of the measured parameters were consistent with those reported in the literature (Wang et al 2008;Fotelli et al 2009;Maunoury-Danger et al 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All these parameters were similar for healthy and declining trees. Similarly, the observed phenological variations of the measured parameters were consistent with those reported in the literature (Wang et al 2008;Fotelli et al 2009;Maunoury-Danger et al 2010).…”
Section: Discussionsupporting
confidence: 91%
“…All the leaf functional variables (LMA, mean leaf surface, percentage of N, d 13 C of total organic matter, and stomatal densities) studied were within the range reported for healthy beech trees in the literature (Aussenac and Ducrey 1977;Balsberg Påhlsson 1989;Keitel et al 2006;Wang et al 2008Wang et al , 2011Closa et al 2010;Bresson et al 2011). All these parameters were similar for healthy and declining trees.…”
Section: Discussionsupporting
confidence: 70%
“…The present study over multiple (five) years with variable V cmax observation contributes to a better understanding of the ecophysiological background of the temporal variability in ecosystem CO 2 budget and its components, of which LAI has already been implicated as the major biophysical determinant of seasonal and interannual variability in ecosystem CO 2 exchange by numerous in situ observation and modelling studies (e.g., Bondeau et al 1999;Barr et al 2004;Saigusa et al 2005). Seasonal growth of single-leaf morphological and photosynthetic characteristics continues to be one of the major focuses of interest in plant physiological ecology (Wilson et al 2000;Xu and Baldocchi 2003;Niinemets et al 2004;Wang et al 2008). This is because the phenomenon reflects the resource acquisition and utilization strategies of species, as well as the response to and influence of the micrometeorological conditions of local environments.…”
Section: Effects Of Temporal Variations In Leaf Photosynthesis and Lamentioning
confidence: 99%
“…But it should also be noted that photosynthetic capacity in single leaves changes throughout the seasons and years (Wilson et al 2000;Muraoka and Koizumi 2005;Wang et al 2008). Canopy photosynthesis comprises the complex consequences of leaf area, canopy architecture, single leaf photosynthetic capacity and meteorological factors such as light incidence, air temperature and humidity, in a non-linear manner Ito et al 2005;Muraoka and Koizumi 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In deciduous forest, although immerged in the more apparent physical changes (leaf flush, expanding and abscission), the seasonal change of biochemical parameters were also noted (e.g. Kodani et al 2002, Wang et al 2008, which indicates the NDVI time series over deciduous forest include both contributions from biophysical and biochemical changes. Wang et al (2007a) found there were close relationships between multiple source vegetation indices and filed measured photosynthetic parameters (V m , J max ) in terms of seasonal variations in three beech forest stands (Fagus crenata).…”
Section: Discussionmentioning
confidence: 99%